P–T CONDITIONS, U/Pb AND 40Ar/39Ar ISOTOPIC AGES OF UHT GRANULITES FROM CAPE KALTYGEI, WESTERN BAIKAL REGION - N. I. Volkova; E. I. Mikheev; A. V. Travin; A. G. Vladimirov; A. S. Mekhonoshin; V. V. Khlestov (Геодинамика и тектонофизика)
The study is focused on metapelitic granulites of Cape Kaltygei (Western Baikal region) that contain a diagnostic mineral assemblage of ultrahigh temperature (UHT) metamorphic rocks (orthopyroxene+sillimanite+quartz). The pseudosection-based thermobarometry yields peak metamorphic temperature and pressure values (T=950 °C, P=~9 kbar) and suggests near-isobaric cooling (IBC) conditions during the retrograde evolution of the granulites. The U/Pb zircon age estimates for metamorphism (~1.87 Ga) support the data published by other researchers. The SHRIMP-II U-Pb dating of zircon cores yields a minimum protolith age of 1.94–1.91 Ga. Biotites and amphiboles from granulites of Cape Kaltygei show the 40Ar/39Ar isotopic ages that are close to the Early Paleozoic accretion-collision system of the Western Baikal region.